ICT security in tax administration - AV protection systems - Muliński, Tomasz (Studia Informatica. System and information technology, 2021)
The article discusses the topic of ICT security in tax administration. This paper presents a study of the security level of endpoints8, servers using three antivirus protection systems. It discusses three independent solutions used to ensure the protection of ICT equipment in public administration.